Kapasitas dan Energi Adsorpsi Humin Terhadap Eosin - A.M., Anshar; S. J., Santosa; S., Sudiono (Al-Kimia, 2015)
Humin is a natural ingredient that is widely available in Indonesia, especially Borneo. Humin is interact and absorb eosin compound that can cause environmental pollution. The interaction between eosin and humin was set on optimum time dan pH so that the humin adsorption would be optimum. This research measured the adsorption capacity and energy required to adsorp eosin on humin by performing various concentration of eosin. The amount of humin adsorption energy against eosin was 34.136 kJ/mol while the adsorption capacity was1, 611 x 10-6mol/g. This indicated that the type of interaction between humin and eosin was chemical interaction.